The impact of the application of agrochemicals on heavy metal pollution in plantation area / Mohd Zahari Abdullah, Nur Syakira Che Nadzir and Fazrul Razman Sulaiman - Abdullah, Mohd Zahari; Che Nadzir, Nur Syakira; Sulaiman, Fazrul Razman (Universiti Teknologi MARA Cawangan Pahang, 2020)
The application of agrochemicals in plantation activities has a potential to pollute the surrounding areas with some levels of heavy metals. The study was conducted to measure the heavy metals content deposited around the site and to evaluate the pollution indexes of the area. The observation obtained was further used to evaluation of the impact of agrichemicals on the surrounding. The mosses and soil samples were digested using a wet digestion method and the heavy metals were analysed by using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES). Four physicochemical parameters including temperature, dissolved oxygen (DO), pH and specific conductance (SpC) were measured in situ. The mean metal concentration order for the moss sample was observed as Zn > Cu > Cr > Ni > Cd > Pb while in the order of Pb > Zn > Cr > Cu > Ni > Cd for the topsoil. For surface water sample, the order of metal concentration was Zn > Pb > (Cd = Cr = Cu) >Ni. The Contamination Factor (CF), Pollution Load Index (PLI) and correlation pair analysis derived from the measured data clearly proved that all samples of mosses, topsoil and surface water have been polluted by the selected heavy metals studied.